The Strategy for Developing the Emotional Intelligence of Student at SMP Muhammadiyah Al-Mujahidin Gunungkidul - Ghaffarah, Linggarati (Universitas Muhammadiyah Yogyakarta, 2025)
A person's ability to receive positive thinking can play an important role in managing, assessing, solving problems, and controlling emotions in themselves and those around them, which is called emotional intelligence. The objectives achieved by researchers were strategies for developing students' emotional intelligence and identifying supporting and inhibiting factors for the development of students' emotional intelligence at Muhammadiyah Al-Mujahidin Middle School, Gunungkidul. Respondents who supported the research were 2 teachers and 6 students. The research was conducted using a qualitative descriptive research method, which uses data collection techniques through observation, interviews, and documentation. Researchers also used source triangulation techniques and engineering triangulation to increase the credibility of the data. The data analysis technique used Miles and Huberman's theory, which consists of 3 stages: data reduction, data presentation, and data verification. Research conducted shows that 1) habituation, learning, and punishment are strategies used to develop emotional intelligence. 2) Supporting factors in developing emotional intelligence through the role of parents, the role of the surrounding environment, students, and attitude values. Meanwhile, inhibiting factors include the influence of friendship, the indifferent role of parents, and previous violations that students have committed. The existence of this development strategy means that the goals of learning activities can be easily achieved, namely developing students' emotional intelligence into better individuals in terms of thoughts, words, and actions. Apart from that, this research can also be a basis for educational institutions to build relationships with parents for a better future. Apart from development in educational institutions, this strategy can also be developed in the family or community environment so that students can become a superior, active, and communicative generation in the future, and it can also be beneficial for the nation and state.